Peran Financial Technology Berbasis Digital Payment System E-Wallet dalam Meningkatkan Literasi Keuangan - Hikmatul Maulidah; Krisdiyawati Krisdiyawati; Erni Unggul Sedya Utami (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the role of financial technology based on the digital payment system e-wallet in improving financial literacy in MSMEs. Financial technology based on the digital payment system e-wallet is a financial service that can help MSME actors to make payment transactions easily and automatically provide financial recording facilities related to cash receipt transactions that occur in the business of MSME actors. There are 4 levels of financial literacy, namely not literate, less literate, sufficient literate, and well literate. Financial literacy in this study was measured by knowledge and understanding, risks and benefits, features, security and confidentiality, and skills in using e-wallet used by MSME owners. The study was conducted on 2 MSME coffee shops that use financial technology based on the digital payment system e-wallet, namely Wiji Kopi and Tradition Ngopi. The type of research in this study is qualitative with a case study approach. This research uses spiral data analysis technique. This study uses primary data and secondary data in the form of interviews, observations, literature studies, and documentation. Research results The application of financial technology based on the digital payment system e-wallet facilitates the business activities of MSME coffee shop actors, especially in terms of managing payment transactions in their business so as to increase the financial literacy of coffee shop MSME actors.